Rapidly rotating stars and their transiting planets: KELT-17b, KELT-19Ab, and KELT-21b in the CHEOPS and TESS era. Issue 2 (25th April 2022) - Garai, Z; Pribulla, T; Kovács, J; Szabó, Gy M; Claret, A; Komžík, R; Kundra, E
ABSTRACT: Rapidly rotating early-type main-sequence stars with transiting planets are interesting in many aspects. Unfortunately, several astrophysical effects in such systems are not well understood yet. Therefore, we performed a photometric mini-survey of three rapidly rotating stars with transiting planets, namely KELT-17b, KELT-19Ab, and KELT-21b, using the Characterising Exoplanets Satellite ( CHEOPS ), complemented with Transiting Exoplanet Survey Satellite ( TESS ) data, and spectroscopic data. We aimed at investigating the spin-orbit misalignment and its photometrical signs, therefore the high-quality light curves of the selected objects were tested for transit asymmetry, transit duration variations, and orbital precession. In addition, we performed transit time variation analyses, obtained new stellar parameters, and refined the system parameters. For KELT-17b and KELT-19Ab, we obtained significantly smaller planet radius as found before. The gravity-darkening effect is very small compared to the precision of CHEOPS data. We can report only on a tentative detection of the stellar inclination of KELT-21, which is about 60 deg. In KELT-17b and KELT-19Ab, we were able to exclude long-term transit duration variations causing orbital precession. The shorter transit duration of KELT-19Ab compared to the discovery paper is probably a consequence of a smaller planet radius. KELT-21b is promising from this viewpoint, but further precise observations are needed. We did not find any convincing evidence for additional objects in the systems.